Sodium ion battery and aging formation method thereof

By using sodium lactonate and 5,6-dihydroxyindole modified modified carbon nanotubes in sodium ion batteries, as well as copolymers of N-vinylpyrrolidone and 1,5-pentanediol diacrylate in sodium ion batteries, combined with step-by-step charging and discharge and multiple vacuum degassing processes, the problem of stable SEI film formation in the sodium ion battery formation process is solved, significantly improving the performance and life of the battery.

CN119852405APending Publication Date: 2025-04-18ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510045191.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the process of decomposition of sodium ion batteries, especially the process of forming a stable SEI film, there are challenges in performance and life, and it is difficult to fully apply the aging process of lithium ion batteries.

Method used

The modified carbon nanotubes modified with sodium lactonate and/or 5,6-dihydroxyindole are used as conductive agents, and in the preparation of the positive electrode sheet of the sodium ion battery, a copolymer of N-vinylpyrrolidone and 1,5-pentanediol diacrylate is used as the dispersant, and the step-by-step charging and discharge and multiple vacuum degassing processes are combined to optimize the aging process of the battery.

Benefits of technology

It significantly improves the pole state of the sodium ion battery, improves the first Coulomb efficiency, positive electrode energy density and cycling performance, and extends the battery's service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852405A_ABST
    Figure CN119852405A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium-ion battery and an aging formation method thereof, and belongs to the technical field of sodium-ion batteries, a conductive agent in a positive plate of the sodium-ion battery is one or more of Super P, graphene, acetylene black, ketjen black, conductive graphite, a carbon nanotube and a modified carbon nanotube, the modified carbon nanotube adopts sodium lactobionate and / or 5, 6-dimethyl-2, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3- and modifying with 2, 6-dihydroxyindole to obtain the product. In the aging formation process, a stepped charging and discharging sequence is adopted, and the sodium ion battery is subjected to aging formation by adopting a multi-time vacuum degassing mode in the discharging step, so that the state of a pole piece can be remarkably improved, and the electrochemical performance of the obtained battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery and an aging formation method thereof. Background Art

[0002] Sodium ion batteries (SIBs) have shown significant application potential in the field of large-scale electrochemical energy storage due to their abundance of sodium resources, cost-effectiveness and high safety. The battery formation process, that is, the first charging process, is a crucial link in battery production and plays a decisive role in the performance and service life of the battery. In the formation process of SIBs, sodium ions (Na + ) is deintercalated from the positive electrode material, passes through the electrolyte and the separator, and finally is embedded in the negative electrode material; during the discharge process, Na + It escapes from the negative electrode material and passes through the electrolyte and the separator back to the positive electrode material.

[0003] The negative electrode material used in SIBs is hard carbon, which differs from the graphite material used in lithium-ion batteries in terms of sodium storage mechanism, which means that the formation aging process of lithium-ion batteries cannot be fully applied to SIBs.

[0004] It can be seen that the formation process of sodium-ion batteries is a key step in their production process and has a profound impact on battery performance and life. In order to achieve high-performance and long-life SIBs, the formation process must be studied and optimized in depth, especially in the formation of a stable SEI film. Summary of the invention

[0005] The object of the present invention is to provide a sodium ion battery and an aging formation method thereof, which can significantly improve the state of the pole piece and enhance the electrochemical performance of the obtained battery.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A method for preparing a positive electrode sheet of a sodium ion battery comprises the following steps: mixing a positive electrode main material, a conductive agent and an adhesive to obtain a mixed powder; then adding a solvent to the mixed powder and stirring to obtain a mixed slurry; placing the mixed slurry under -0.7 to -0.1 Pa and stirring to perform a vacuum degassing treatment; then coating the obtained slurry on an aluminum foil, drying it, and cutting it into pieces to obtain a positive electrode sheet.

[0007] Preferably, the mass ratio of the positive electrode main material, the conductive agent, and the adhesive is 70-95:2-6:1-5.

[0008] Preferably, the solvent is NMP (N-methylpyrrolidone), and the mass ratio of the positive electrode main material to NMP is 5-15:1.

[0009] Furthermore, the main material of the positive electrode is one of layered oxides, Prussian blue and its analogs, and polyanionic compounds.

[0010] Furthermore, the conductive agent is one or more of Super P, graphene, acetylene black, Ketjen black, conductive graphite, carbon nanotubes and modified carbon nanotubes, wherein the modified carbon nanotubes are modified by sodium lactobionate and / or 5,6-dihydroxyindole.

[0011] Furthermore, the adhesive includes PVDF and a dispersant, and the dispersant is a homopolymer or copolymer of N-vinyl pyrrolidone.

[0012] Preferably, in the adhesive, the mass ratio of PVDF to dispersant is 1-5:1.

[0013] The use of modified carbon nanotubes containing sodium lactobionate and / or 5,6-dihydroxyindole modification groups as conductive agents can significantly improve the first coulombic efficiency of the obtained sodium ions, the positive electrode energy density and the cycle performance. This may be because the modified carbon nanotubes, after being modified by sodium lactobionate and / or 5,6-dihydroxyindole, help to form a good conductive network in the obtained positive electrode slurry, reduce the internal resistance and are not easy to polarize, thereby improving the performance of the obtained battery. After the carbon nanotubes are modified with sodium lactobionate and / or 5,6-dihydroxyindole, the surface of the obtained modified carbon nanotubes forms a carbonized structure composed of sodium lactobionate and / or 5,6-dihydroxyindole related groups, that is, the microstructure of the modified carbon nanotubes is changed, which is conducive to the embedding and de-embedding of sodium ions, and can promote the diffusion of sodium ions in the electrolyte, making up for the lack of slow diffusion of sodium ions due to their large ionic radius. In addition, the introduction of heteroatoms during the modification of carbon nanotubes also helps to improve the conductivity of the obtained positive electrode slurry and improve the electrochemical performance.

[0014] According to one aspect of the present invention, there is provided a sodium ion battery positive electrode sheet prepared by the above method, comprising: a base layer, and a functional layer attached to the base layer; the base layer is aluminum foil; the functional layer comprises a slurry prepared by using a positive electrode main material, a conductive agent, and an adhesive, the conductive agent is one or more of Super P, graphene, acetylene black, Ketjen black, conductive graphite, carbon nanotubes and modified carbon nanotubes, wherein the modified carbon nanotubes are obtained by modification with sodium lactobionate and / or 5,6-dihydroxyindole.

[0015] According to one aspect of the present invention, a method for preparing a sodium ion battery cell is provided, which comprises using a hard carbon negative electrode sheet and a PP separator, in combination with the positive electrode sheet obtained above, assembling them in a stacking manner, and then packaging them with an aluminum-plastic film, injecting an electrolyte, and obtaining a battery cell.

[0016] Furthermore, the electrolyte contains NaClO 4 、NaOTf、NaPF 6The solvent in the electrolyte is one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and tris (2,2,2-trifluoroethyl) borate.

[0017] According to one aspect of the present invention, there is provided a method for aging and forming a battery cell, comprising the following steps: S1. Transfer the injected sodium ion battery to a 30-45°C environment for electrolyte infiltration for 18-48 hours; after infiltration, transfer the battery to a 25°C environment for cooling; S2. Place the cooled battery cell into a high temperature and pressure forming device, set the temperature to 25-36°C and the forming pressure to 0.2-0.8MPa; after the temperature and pressure of the battery reach the set value, use the following step-by-step charging and discharging method for formation. The specific steps are as follows: a) In the first stage, constant current charging is performed to 10-20% of the reversible capacity, the charging current range is 0.05~0.15C, and the charging time is 1-3h; b) The second stage is constant current charging, charging to 20-40% of the reversible capacity, the charging current range is 0.15C~0.2C, and the charging time is 1-3h; c) The third stage is constant current charging, charging to a battery voltage of 3.00-4.25V, with a charging current range of 0.2C~0.3C; d) The fourth stage is constant current discharge, discharging to a battery voltage of 2.0-3.0V, with a discharge current range of 0.3C~0.5C; S3. After the battery is cooled to 25°C, the first vacuum degassing is performed to remove the gas generated inside the battery; S4. Place the degassed battery into a high temperature and pressurized formation device, set the temperature to 25-36°C, and the formation pressure to 0.2-0.8MPa; after the temperature and pressure of the battery reach the set value, perform constant current charging, charge to the battery voltage of 3.85-3.9V, and the charging current range is 0.2C~0.5C; S5. Remove the battery from step S4 and transfer it to an environment of 35-45°C for aging for 12-48h; S6. After the aging is completed, the battery is cooled to room temperature and the battery is subjected to a second vacuum degassing to remove the gas generated inside the battery.

[0018] The use of a step-by-step charge and discharge sequence, and the use of multiple vacuum degassing in the discharge step to age the sodium-ion battery, helps to improve the performance of the resulting battery. This may be because the multiple degassing process helps to build a stable solid electrolyte interface membrane, improve the sodium storage performance of the Yintan negative electrode material, and thus improve the consistency and cycle life of the battery.

[0019] According to one aspect of the present invention, there is provided a method for preparing modified carbon nanotubes, wherein the modified carbon nanotubes have a modification group of sodium lactobionate and / or 5,6-dihydroxyindole, comprising the following steps: Using concentrated H 2 SO 4 and concentrated HNO 3 The carbon nanotubes are acidified with a mixed acid. After the acidification is completed, the solid product is washed to neutrality; the obtained solid product is dried and dispersed in DMF, and after adding DCC and DMAP, sodium lactobionate and 5,6-dihydroxyindole are added. Under a nitrogen atmosphere, the mixture is heated to 110-160°C and reacted for 12-48 hours to modify the acidified carbon nanotubes with hydroxyl groups; then the mixture is heated to 600-700°C and reacted for 1-4 hours. The obtained product is washed with ethanol and dried to obtain modified carbon nanotubes.

[0020] Preferably, concentrated H 2 SO 4 and concentrated HNO 3 The volume ratio is 1-3:1-3; Preferably, the mass volume ratio of carbon nanotubes to mixed acid is 1 g:20-50 mL; Preferably, the acidification temperature is 120-160° C. and the acidification time is 45-120 min.

[0021] Preferably, after the acidification is completed, ultrapure water is used to wash the acidified carbon nanotubes.

[0022] Preferably, the mass volume ratio of carbon nanotubes to DMF is 1 g:3-10 mL; Preferably, the mass ratio of DCC to DMAP is 8-20:1; Preferably, the mass ratio of carbon nanotubes to DCC is 1:2-6; Preferably, the mass ratio of 5,6-dihydroxyindole to sodium lactobionate is 1:1-3; Preferably, the mass ratio of carbon nanotubes to 5,6-dihydroxyindole is 1:0.5-3.

[0023] According to one aspect of the present invention, there is provided a method for preparing a dispersant, wherein the dispersant is a homopolymer of N-vinyl pyrrolidone, comprising the following steps: N-vinyl pyrrolidone is dissolved in DMF to obtain a DMF solution of N-vinyl pyrrolidone, hydrogen peroxide is added as a catalyst, azobisisobutyl cyanide is added as an initiator, and polymerization is carried out at 40-60° C. for 2-6 hours under nitrogen protection. After cooling, the solvent is removed by suction filtration and rotary evaporation, and the obtained solid product is washed with deionized water, and vacuum dried at 35-55° C. for 4-8 hours to obtain a dispersant.

[0024] Preferably, in the DMF solution of N-vinyl pyrrolidone, the mass fraction of N-vinyl pyrrolidone is 30-60%; Preferably, the mass ratio of N-vinyl pyrrolidone to hydrogen peroxide is 5-15:1; Preferably, the mass ratio of N-vinyl pyrrolidone to azobisisobutyl cyanide is 50-120:1.

[0025] Furthermore, a method for preparing a dispersant is provided, wherein the dispersant is a copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate, comprising the following steps: N-vinyl pyrrolidone and 1,5-pentanediol diacrylate are dissolved in DMF to obtain a DMF solution of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate; hydrogen peroxide is added as a catalyst, azobisisobutyl cyanide is added as an initiator, and a polymerization reaction is carried out at 40-60° C. for 2-6 hours under nitrogen protection, and after cooling, the solvent is removed by suction filtration and rotary evaporation, and the obtained solid product is washed with deionized water, and vacuum dried at 35-55° C. for 4-8 hours to obtain a dispersant.

[0026] Preferably, in the DMF solution of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate, the mass fraction of N-vinyl pyrrolidone is 30-60%, and the mass fraction of 1,5-pentanediol diacrylate is 3-20%; Preferably, the mass ratio of N-vinyl pyrrolidone to hydrogen peroxide is 5-15:1; Preferably, the mass ratio of N-vinyl pyrrolidone to azobisisobutyl cyanide is 50-120:1.

[0027] In the process of preparing the positive electrode sheet of the sodium ion battery, the conductive agent is modified with carbon nanotubes modified with sodium lactobionate and 5,6-dihydroxyindole, and the dispersant in the adhesive used in combination is a copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate instead of the homopolymer of N-vinyl pyrrolidone, which can further improve the first coulomb efficiency, positive electrode energy density and cycle performance of the obtained sodium ion battery. This may be because the modified carbon nanotubes with a carbonized structure formed by sodium lactobionate and 5,6-dihydroxyindole related groups on the surface can further promote the diffusion of sodium ions in the electrolyte in the process of cooperating with the copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate.

[0028] Compared with the prior art, the present invention has the following beneficial effects: 1. In the process of sodium ion battery aging, a step-by-step charging and discharging sequence and two vacuum degassing processes are adopted, which can significantly improve the state of the obtained electrode and greatly improve the first coulombic efficiency, positive electrode energy density and cycle performance of the obtained battery.

[0029] 2. Sodium lactobionate and / or 5,6-dihydroxyindole are used to modify carbon nanotubes, and the surface of the modified carbon nanotubes has a carbonized structure formed by related groups of sodium lactobionate and / or 5,6-dihydroxyindole; using such modified carbon nanotubes as conductive agents can significantly improve the first coulombic efficiency of sodium ions, positive electrode energy density and cycle performance. This may be because the carbonized structure of sodium lactobionate and / or 5,6-dihydroxyindole formed on the surface of the modified carbon nanotubes helps to form a good conductive network in the positive electrode slurry, reduce internal resistance and is not easy to polarize, thereby improving the performance of the resulting battery.

[0030] 3. In the process of preparing the positive electrode of the sodium ion battery, the conductive agent is made of sodium lactobionate and carbon nanotubes modified with 5,6-dihydroxyindole, and the dispersant in the adhesive used in combination is made of a copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate instead of the homopolymer of N-vinyl pyrrolidone, which can further improve the first coulombic efficiency, positive electrode energy density and cycle performance of the obtained sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a photo of the electrode obtained according to Example 1 of the present invention; Figure 2 This is a photograph of the pole piece obtained according to Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] Example 1 Preparation of battery positive electrode The positive electrode material, conductive agent and adhesive were mixed and stirred at 500r / min for 30min to obtain a mixed powder; then the solvent was added to the mixed powder and stirred at 500r / min for 2h to obtain a mixed slurry. The mixed slurry was placed under -0.5MPa and stirred at 50r / min for 60min for vacuum degassing. Then the obtained slurry was coated on aluminum foil with a single-sided coating amount of 0.015g / cm 2 , placed in a vacuum drying oven at 80°C for 8 hours, after the solvent is completely evaporated, cut into pieces to obtain the positive electrode sheet.

[0034] The cathode material is Prussian blue, the conductive agent is modified carbon nanotubes, the modified carbon nanotubes have sodium lactobionate and / or 5,6-dihydroxyindole modification groups, and the adhesive includes PVDF and a dispersant; the mass ratio of the cathode material, the conductive agent, and the adhesive is 90:5:3; in the adhesive, the mass ratio of PVDF to the dispersant is 3:1, and the dispersant is a homopolymer of N-vinyl pyrrolidone. The solvent is NMP, and the mass ratio of the cathode material to NMP is 8:1.

[0035] Wherein, the preparation method of modified carbon nanotubes is as follows: Using concentrated H 2 SO 4 and concentrated HNO 3 The carbon nanotubes are acidified with a mixed acid. After the acidification is completed, the solid product is washed to neutrality; the obtained solid product is dried and dispersed in DMF, and after adding DCC and DMAP, sodium lactobionate and 5,6-dihydroxyindole are added. Under a nitrogen atmosphere, the mixture is heated to 120°C and reacted for 24 hours to modify the acidified carbon nanotubes with hydroxyls; then the mixture is heated to 650°C and reacted for 2 hours. The obtained product is washed with ethanol and dried to obtain modified carbon nanotubes.

[0036] Concentrated H 2 SO 4 and concentrated HNO 3 The volume ratio is 1:1, the mass volume ratio of carbon nanotubes and mixed acid is 1g:30mL; the acidification temperature is 150℃, and the acidification time is 90min.

[0037] After the acidification is completed, the acidified carbon nanotubes are washed with ultrapure water.

[0038] The mass volume ratio of carbon nanotubes to DMF is 1 g:5 mL; the mass ratio of DCC to DMAP is 10:1, and the mass ratio of carbon nanotubes to DCC is 1:3; the mass ratio of 5,6-dihydroxyindole to sodium lactobionate is 1:2, and the mass ratio of carbon nanotubes to 5,6-dihydroxyindole is 1:1.

[0039] The preparation method of the dispersant is as follows: N-vinyl pyrrolidone was dissolved in DMF to obtain a DMF solution of N-vinyl pyrrolidone, hydrogen peroxide was added as a catalyst, azobisisobutyl cyanide was added as an initiator, and polymerization was carried out at 50°C for 4 hours under nitrogen protection. After cooling, the solvent was removed by suction filtration and rotary evaporation, and the obtained solid product was washed with deionized water and vacuum dried at 40°C for 6 hours to obtain a dispersant.

[0040] Wherein, in the DMF solution of N-vinyl pyrrolidone, the mass fraction of N-vinyl pyrrolidone is 40%; the mass ratio of N-vinyl pyrrolidone to hydrogen peroxide is 10:1; and the mass ratio of N-vinyl pyrrolidone to azobisisobutylcyanide is 80:1.

[0041] Preparation of battery cells A hard carbon negative electrode sheet and a PP separator are used in combination with the positive electrode sheet obtained above, assembled in a stacking manner, and then packaged with an aluminum-plastic film and injected with an electrolyte to obtain a battery cell.

[0042] The electrolyte contains NaOTf and NaPF 6 The concentrations of the two are 0.5 mol / L and 0.8 mol / L respectively; the solvent in the electrolyte is diethylene glycol dimethyl ether and 1,3-dioxolane, and the volume ratio of the two is 1:1.

[0043] Aging of battery cells S1. Transfer the injected sodium ion battery to a 40°C environment for electrolyte infiltration for 24 hours; after infiltration, transfer the battery to a 25°C environment for cooling; S2. Place the cooled battery cell into a high temperature and pressure forming device, set the temperature to 30°C and the forming pressure to 0.5MPa; after the temperature and pressure of the battery reach the set value, use the following step-by-step charging and discharging method for formation. The specific steps are as follows: a) In the first stage, the battery is charged at a constant current to 15% of the reversible capacity. The charging current range is 0.05-0.15C and the charging time is 2h. b) The second stage is constant current charging, charging to 30% of the reversible capacity, the charging current range is 0.15C~0.2C, and the charging time is 2h; c) The third stage is constant current charging, charging to the battery voltage of 3.75V, and the charging current range is 0.2C~0.3C; d) The fourth stage is constant current discharge, discharging to the battery voltage of 2.7V, and the discharge current range is 0.3C~0.5C; S3. After the battery is cooled to 25°C, the first vacuum degassing is performed to remove the gas generated inside the battery; S4. Place the degassed battery into a high temperature and pressurized formation device, set the temperature to 30°C and the formation pressure to 0.5MPa; after the temperature and pressure of the battery reach the settings, perform constant current charging until the battery voltage reaches 3.85-3.9V, and the charging current range is 0.2C~0.5C.

[0044] S5. Take out the battery in step S4 and transfer it to a 40°C environment for aging for 24 hours.

[0045] S6. After the aging is completed, the battery is cooled to room temperature and the battery is subjected to a second vacuum degassing to remove the gas generated inside the battery.

[0046] The pole piece obtained in this embodiment is shown in Figure 1 .

[0047] Example 2 The difference between this embodiment and embodiment 1 is that: In the preparation process of the positive electrode sheet of the battery, the positive electrode main material is Prussian blue, the conductive agent is modified carbon nanotubes, and the adhesive includes PVDF and a dispersant; the mass ratio of the positive electrode main material, the conductive agent, and the adhesive is 90:7:3; in the adhesive, the mass ratio of PVDF to the dispersant is 3:1, and the dispersant is a homopolymer of N-vinyl pyrrolidone. The preparation methods of the modified carbon nanotubes and the dispersant are the same as those in Example 1.

[0048] The other conditions and steps were the same.

[0049] Example 3 The difference between this embodiment and embodiment 1 is that: In the process of preparing the positive electrode sheet of the battery, the positive electrode main material is Prussian blue, the conductive agent is modified carbon nanotubes, and the adhesive includes PVDF and a dispersant; the mass ratio of the positive electrode main material, the conductive agent, and the adhesive is 90:10:3; in the adhesive, the mass ratio of PVDF to the dispersant is 3:1, and the dispersant is a homopolymer of N-vinyl pyrrolidone. The preparation methods of the modified carbon nanotubes and the dispersant are the same as those in Example 1.

[0050] The other conditions and steps were the same.

[0051] Example 4 The difference between this embodiment and embodiment 1 is that: In the process of preparing the positive electrode of the battery, the adhesive includes PVDF and a dispersant, and the dispersant is a copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate. The preparation method of the dispersant is as follows: N-vinyl pyrrolidone and 1,5-pentanediol diacrylate were dissolved in DMF to obtain a DMF solution of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate, wherein the mass fraction of N-vinyl pyrrolidone was 40% and the mass fraction of 1,5-pentanediol diacrylate was 5%. Hydrogen peroxide was added as a catalyst, and azobisisobutyl cyanide was added as an initiator. Under nitrogen protection, polymerization was carried out at 50°C for 4 hours. After cooling, the solvent was removed by suction filtration and rotary evaporation. The obtained solid product was washed with deionized water and vacuum dried at 40°C for 6 hours to obtain a dispersant. The mass ratio of N-vinyl pyrrolidone to hydrogen peroxide was 10:1; the mass ratio of N-vinyl pyrrolidone to azobisisobutyl cyanide was 80:1.

[0052] The preparation method of modified carbon nanotubes is the same as that in Example 1.

[0053] The other conditions and steps were the same.

[0054] Example 5 In the process of preparing the positive electrode of the battery, the adhesive includes PVDF and a dispersant, and the dispersant is a copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate. The preparation method of the dispersant is as follows: N-vinyl pyrrolidone and 1,5-pentanediol diacrylate were dissolved in DMF to obtain a DMF solution of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate, wherein the mass fraction of N-vinyl pyrrolidone was 40% and the mass fraction of 1,5-pentanediol diacrylate was 10%. Hydrogen peroxide was added as a catalyst, and azobisisobutyl cyanide was added as an initiator. Under nitrogen protection, polymerization was carried out at 50°C for 4 hours. After cooling, the solvent was removed by suction filtration and rotary evaporation. The obtained solid product was washed with deionized water and vacuum dried at 40°C for 6 hours to obtain a dispersant. Among them, the mass ratio of N-vinyl pyrrolidone to hydrogen peroxide was 10:1; the mass ratio of N-vinyl pyrrolidone to azobisisobutyl cyanide was 80:1.

[0055] The preparation method of modified carbon nanotubes is the same as that in Example 1.

[0056] The other conditions and steps were the same.

[0057] Comparative Example 1 The difference between this embodiment and embodiment 1 is that: During the preparation of the modified carbon nanotubes, 5,6-dihydroxyindole was replaced with an equal mass of sodium lactobionate.

[0058] The other conditions and steps were the same.

[0059] Comparative Example 2 The difference between this embodiment and embodiment 1 is that: During the preparation of modified carbon nanotubes, sodium lactobionate was replaced with an equal mass of 5,6-dihydroxyindole.

[0060] The other conditions and steps were the same.

[0061] Comparative Example 3 The difference between this embodiment and embodiment 1 is that: In the preparation process of the battery positive electrode sheet, the main positive electrode material is Prussian blue, the conductive agent is carbon nanotubes, and the adhesive includes PVDF; the mass ratio of the positive electrode main material, the conductive agent, and the adhesive is 90:5:3.

[0062] The other conditions and steps were the same.

[0063] Comparative Example 4 The difference between this embodiment and embodiment 1 is that: During the aging formation process of the battery cell, step S3 is omitted, and after the four stages of stepwise charging and discharging in step S2 are completed, cross-current charging is directly performed. Other conditions and steps are the same.

[0064] The electrode obtained in this comparative example is shown in Figure 2 .contrast Figure 1 and Figure 2 It can be seen that multiple vacuum degassing processes during the aging and formation of sodium-ion batteries can significantly improve the state of the electrode.

[0065] Test example Battery tests were performed on the batteries prepared in Examples 1-5 and Comparative Examples 1-4, respectively.

[0066] The constant current charge-discharge test and cycle life test of the battery were carried out by Xinwei CT4000, and the voltage and electrochemical impedance test of the cyclic voltammetry test were carried out by Chenhua CHI760D electrochemical workstation. The test voltage window was 2.0-4.5 V, and the current density was 1 C=100 mA g -1 .

[0067] For the batteries obtained in Examples 1-5 and Comparative Examples 1-4, the first charge and discharge capacity was tested at a 50C rate and the first coulombic efficiency was calculated. The results of the first coulombic efficiency test are shown in Table 1.

[0068] Table 1 The first coulombic efficiency test results of each embodiment and comparative example

[0069] Referring to the data in Table 1, the first coulombic efficiency of the batteries obtained in Examples 1-5 and Comparative Examples 1-3 increased by 13.9%, 16.9%, 18.5%, 20.1%, 21.5%, 10.5%, 11.6% and 5.3% respectively, compared with Comparative Example 4. It can be seen that in the aging formation process of the sodium ion battery, compared with the process of one vacuum degassing, taking two vacuum degassing can significantly improve the first coulombic efficiency of the obtained battery.

[0070] Compared with Comparative Example 3, the first coulombic efficiency of the batteries obtained in Examples 1-5 and Comparative Example 1-2 increased by 8.1%, 10.9%, 12.5%, 14.0%, 15.3%, 4.8% and 5.9%, respectively. It can be seen that, compared with carbon nanotubes, the use of modified carbon nanotubes as a conductive agent can significantly improve the first coulombic efficiency of sodium ion batteries. The first coulombic efficiency of the batteries obtained in Examples 1-3 is on an upward trend. It can be seen that in the process of preparing the positive electrode slurry of the sodium ion battery, increasing the amount of the modified carbon nanotubes as a conductive agent within a certain range is helpful to improve the first efficiency of the obtained sodium ion battery.

[0071] That is to say, compared with the unmodified carbon nanotubes, the modified carbon nanotubes have a more significant effect on the first coulombic efficiency of the obtained sodium ion battery. Combined with the data of Comparative Examples 1-2, it can be seen that compared with the use of sodium lactobionate alone or 5,6-dihydroxyindole alone as a modifier, the use of sodium lactobionate and 5,6-dihydroxyindole as modifiers in the carbon nanotube modification process has a more significant effect on the first coulombic efficiency of the sodium ion battery.

[0072] Compared with Example 1, the first coulombic efficiency of the battery obtained in Examples 4-5 was increased by 5.4% and 6.6%, respectively. It can be seen that in the process of preparing the positive electrode of the sodium ion battery, the conductive agent is the carbon nanotube modified by sodium lactobionate and 5,6-dihydroxyindole, and the dispersant in the adhesive used is the copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate instead of the homopolymer of N-vinyl pyrrolidone, which can further improve the first coulombic efficiency of the obtained sodium ion battery; and within a certain range, the first coulombic efficiency of the obtained sodium ion battery is positively correlated with the amount of the copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate in the adhesive.

[0073] For the batteries prepared in Examples 1-5 and Comparative Examples 1-4, the capacity of the batteries was obtained by charging to 4.0V at 0.5C constant current and constant voltage, and discharging to 1.5V at 0.5C. The weight of the battery cell was measured with a balance, and the energy density of the battery cell was calculated. The positive electrode energy density test results are shown in Table 2.

[0074] Table 2 Test results of positive electrode energy density of various embodiments and comparative examples

[0075] Referring to the data in Table 2, the positive electrode energy density of the batteries obtained in Examples 1-5 and Comparative Examples 1-3 increased by 17.7%, 22.1%, 25.7%, 30.1%, 32.7%, 8.8%, 10.6% and 5.3% respectively, compared with Comparative Example 4. It can be seen that in the aging formation process of the sodium ion battery, compared with the process of one vacuum degassing, taking two vacuum degassing can significantly improve the positive electrode energy density of the obtained battery.

[0076] Compared with Comparative Example 3, the positive electrode energy density of the batteries obtained in Examples 1-5 and Comparative Example 1-2 increased by 11.8%, 16.0%, 19.3%, 23.5%, 26.1%, 3.4% and 5.0%, respectively. It can be seen that, compared with carbon nanotubes, the use of modified carbon nanotubes as a conductive agent can significantly improve the positive electrode energy density of sodium ion batteries. The positive electrode energy density of the batteries obtained in Examples 1-3 is on an upward trend. It can be seen that in the process of preparing the positive electrode slurry of the sodium ion battery, increasing the amount of modified carbon nanotubes as a conductive agent within a certain range is helpful to improve the initial efficiency of the obtained sodium ion battery.

[0077] That is to say, compared with the unmodified carbon nanotubes, the modified carbon nanotubes have a more significant effect on the positive electrode energy density of the obtained sodium ion battery. Combined with the data of Comparative Examples 1-2, it can be seen that compared with the use of sodium lactobionate alone or 5,6-dihydroxyindole alone as a modifier, the use of sodium lactobionate and 5,6-dihydroxyindole as modifiers in the carbon nanotube modification process has a more significant effect on the positive electrode energy density of the sodium ion battery.

[0078] Compared with Example 1, the positive electrode energy density of the battery obtained in Examples 4-5 was increased by 10.5% and 12.8%, respectively. It can be seen that in the process of preparing the positive electrode sheet of the sodium ion battery, the conductive agent is the carbon nanotube modified by sodium lactobionate and 5,6-dihydroxyindole, and the dispersant in the adhesive used is the copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate instead of the homopolymer of N-vinyl pyrrolidone, which can further improve the positive electrode energy density of the obtained sodium ion battery; and within a certain range, the positive electrode energy density of the obtained sodium ion battery is positively correlated with the amount of the copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate in the adhesive.

[0079] For the batteries prepared in Examples 1-5 and Comparative Examples 1-4, the cycle performance was tested for 500 cycles using a 1C rate charge / discharge test. The capacity retention test results are shown in Table 3.

[0080] Table 3 Capacity retention test results after 500 cycles of each embodiment and comparative example

[0081] Referring to the data in Table 3, the capacity retention rates of the batteries obtained in Examples 1-5 and Comparative Examples 1-3 after 500 cycles were increased by 14.2%, 16.4%, 18.1%, 20.4%, 9.1%, 10.7%, 10.6% and 5.5%, respectively, compared with Comparative Example 4. It can be seen that in the aging and formation process of sodium ion batteries, compared with the process of one vacuum degassing, two vacuum degassing processes can significantly improve the capacity retention rate of the obtained battery.

[0082] Compared with Comparative Example 3, the capacity retention rates of the batteries obtained in Examples 1-5 and Comparative Example 1-2 after 500 cycles were increased by 8.3%, 10.4%, 12.6%, 14.2%, 15.9%, 3.4% and 4.9%, respectively. It can be seen that, compared with carbon nanotubes, the use of modified carbon nanotubes as a conductive agent can significantly improve the capacity retention rate of sodium ion batteries. The capacity retention rate of the batteries obtained in Examples 1-3 is on an upward trend. It can be seen that in the process of preparing the positive electrode slurry of the sodium ion battery, increasing the amount of the modified carbon nanotubes as a conductive agent within a certain range is helpful to improve the initial efficiency of the obtained sodium ion battery.

[0083] That is to say, compared with the unmodified carbon nanotubes, the modified carbon nanotubes have a more significant effect on the capacity retention rate of the obtained sodium ion battery. Combined with the data of Comparative Examples 1-2, it can be seen that compared with the use of sodium lactobionate alone or 5,6-dihydroxyindole alone as a modifier, the use of sodium lactobionate and 5,6-dihydroxyindole as modifiers in the carbon nanotube modification process has a more significant effect on the capacity retention rate of the sodium ion battery.

[0084] Compared with Example 1, the capacity retention rates of the batteries obtained in Examples 4-5 after 500 cycles were increased by 5.4% and 7.1%, respectively. It can be seen that in the process of preparing the positive electrode sheet of the sodium ion battery, the conductive agent is the carbon nanotube modified with sodium lactobionate and 5,6-dihydroxyindole, and the dispersant in the adhesive used is the copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate instead of the homopolymer of N-vinyl pyrrolidone, which can further improve the capacity retention rate of the obtained sodium ion battery; and within a certain range, the capacity retention rate of the obtained sodium ion battery is positively correlated with the amount of the copolymer of N-vinyl pyrrolidone and 1,5-pentanediol diacrylate in the adhesive.

[0085] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.

[0086] The above-described embodiments provide a detailed description of the technical solution of the present invention. It should be understood that the above-described embodiments are only specific embodiments of the present invention and are not intended to limit the present invention. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a positive electrode sheet for a sodium ion battery, comprising mixing a positive electrode main material, a conductive agent and an adhesive to obtain a mixed powder; then adding a solvent to the mixed powder and stirring to obtain a mixed slurry; placing the mixed slurry under -0.7 to -0.1 Pa and stirring to perform a vacuum degassing treatment, then coating the obtained slurry on an aluminum foil, drying it, and cutting it into pieces to obtain a positive electrode sheet; The conductive agent is one or more of Super P, graphene, acetylene black, Ketjen black, conductive graphite, carbon nanotubes and modified carbon nanotubes, wherein: The modified carbon nanotubes are obtained by modification with sodium lactobionate and / or 5,6-dihydroxyindole.

2. The method for preparing a positive electrode sheet for a sodium ion battery according to claim 1, characterized in that: The adhesive comprises PVDF and a dispersant, and the dispersant is a homopolymer or a copolymer of N-vinyl pyrrolidone.

3. The method for preparing a positive electrode sheet for a sodium ion battery according to claim 1, characterized in that: The mass ratio of the positive electrode main material, the conductive agent and the adhesive is 70-95:2-6:1-5.

4. The method for preparing a positive electrode sheet for a sodium ion battery according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes is as follows: The carbon nanotubes are acidified with a mixed acid of concentrated H2SO4 and concentrated HNO3. After the acidification is completed, the solid product is washed to neutrality. The obtained solid product is dried and dispersed in DMF. After adding DCC and DMAP, sodium lactobionate and 5,6-dihydroxyindole are added. The mixture is heated to 110-160°C in a nitrogen atmosphere and reacted for 12-48 hours to modify the acidified carbon nanotubes with hydroxyl groups. The mixture is then heated to 600-700°C and reacted for 1-4 hours. The obtained product is washed with ethanol and dried to obtain modified carbon nanotubes.

5. The method for preparing a positive electrode sheet for a sodium ion battery according to claim 4, characterized in that: The volume ratio of concentrated H2SO4 and concentrated HNO3 is 1-3:1-3; The mass volume ratio of carbon nanotubes to mixed acid is 1g:20-50mL; The acidification temperature is 120-160°C, and the acidification time is 45-120 minutes.

6. The method for preparing a positive electrode sheet for a sodium ion battery according to claim 4, characterized in that: The mass volume ratio of carbon nanotubes to DMF is 1 g:3-10 mL; The mass ratio of DCC to DMAP is 8-20:1; The mass ratio of carbon nanotubes to DCC is 1:2-6; The mass ratio of 5,6-dihydroxyindole to sodium lactobionate is 1:1-3; The mass ratio of carbon nanotubes to 5,6-dihydroxyindole is 1:0.5-3.

7. A sodium ion battery positive electrode sheet, characterized in that: include: A base layer and a functional layer attached to the base layer; the base layer is aluminum foil; the functional layer comprises a slurry prepared by using a positive electrode main material, a conductive agent, and an adhesive, the conductive agent is one or more of Super P, graphene, acetylene black, Ketjen black, conductive graphite, carbon nanotubes and modified carbon nanotubes, wherein the modified carbon nanotubes are obtained by modifying with sodium lactobionate and / or 5,6-dihydroxyindole.

8. An aging formation method for a sodium ion battery, the sodium ion battery comprising the sodium ion battery positive electrode sheet according to claim 7; comprising the following steps: S1. Transfer the injected sodium ion battery to a 30-45°C environment for electrolyte infiltration for 18-48 hours; after infiltration, transfer the battery to a 25°C environment for cooling; S2. Place the cooled battery cell into a high temperature and pressure forming device, set the temperature to 25-36°C and the forming pressure to 0.2-0.8MPa; after the temperature and pressure of the battery reach the set value, use a step-by-step charging and discharging method for forming; S3. After the battery is cooled to 25°C, the first vacuum degassing is performed to remove the gas generated inside the battery; S4. Place the degassed battery into a high temperature and pressurized formation device, set the temperature to 25-36°C, and the formation pressure to 0.2-0.8MPa; after the temperature and pressure of the battery reach the set value, perform constant current charging, charge to the battery voltage of 3.85-3.9V, and the charging current range is 0.2C~0.5C; S5. Remove the battery from step S4 and transfer it to an environment of 35-45°C for aging for 12-48h; S6. After the aging is completed, the battery is cooled to room temperature and the battery is subjected to a second vacuum degassing to remove the gas generated inside the battery.

9. The aging formation method of a sodium ion battery according to claim 8, characterized in that: The step-by-step charging and discharging method in step S2 has the following specific steps: a) In the first stage, constant current charging is performed to 10-20% of the reversible capacity, the charging current range is 0.05~0.15C, and the charging time is 1-3h; b) The second stage is constant current charging, charging to 20-40% of the reversible capacity, the charging current range is 0.15C~0.2C, and the charging time is 1-3h; c) The third stage is constant current charging, charging to a battery voltage of 3.00-4.25V, with a charging current range of 0.2C~0.3C; d) The fourth stage is constant current discharge, discharging to a battery voltage of 2.0-3.0V, with a discharge current range of 0.3C~0.5C.